Look to the stars - Aldrin, Buzz.; Minor, Wendell (New York : G.P. Putnam's, 2009)
Chronicles the history of space exploration, looking at space pioneers, programs, rockets, missions, and related topics from the perspective of Buzz Aldrin, one of the few astronauts to have walked on the moon.
Includes bibliographical references (p. 40).
Booklist.
Publisher's Weekly.
School Library Journal.
6.1
K-3
Keywords: Aldrin, Buzz -- Juvenile literature; Aldrin, Buzz; Aldrin, Buzz; Astronautics -- Juvenile literature; Interplanetary voyages -- Juvenile literature; Space flights -- Juvenile literature; Astronautics; Interplanetary voyages; Space flights; Astronautics; Interplanetary voyages; Voyages and travels; Outer space -- Exploration -- Juvenile literature; Outer space -- Exploration; Outer space -- Exploration